Stalled Racial Progress and Japanese Trade in the 1970s and 1980s - Mary Kate Batistich; Timothy N. Bond (Institute of Labor Economics (IZA), 2019)
Many of the positive economic trends coming out of the Civil Rights Era for black men stagnated or reversed during the late 1970s and early 1980s. These changes were concurrent with a rapid rise in import competition from Japan. We assess the impact of this trade shock on racial disparities using commuting zone level variation in exposure. We find it decreased black manufacturing employment, labor force participation, and median earnings, and increased public assistance recipiency. However these manufacturing losses for blacks were offset by increased white manufacturing employment. This compositional shift appears to have been caused by skill upgrading in the manufacturing sector. Losses were concentrated among black high school dropouts and gains among college educated whites. We also see a shifting of manufacturing employment towards professionals, engineers, and college educated production workers. We find no evidence the heterogeneous effects of import competition can be explained by unionization, prejudice, or changes in spatial mismatch. Our results can explain 66-86% of the relative decrease in black manufacturing employment, 17-23% of the relative rise in black non-labor force participation, and 34-44% of the relative decline in black median male earnings from 1970-1990.
Keywords: F14; J31; F14; N32; N62; 330; race; trade; import competition; black-white wage gap; Japan